Business Combinations in the '60s: A Canadian Profile (Book). - Sterling, Robert R.; Briloff, Abraham J. (The Accounting Review, 1971)
Reviews the book "Business Combinations in the '60s: A Canadian Profile," by S.A. Martin, S.N. Laiken and D.F. Haslam.